Etiology and clinical profile of COPD in non-smoker in urban area - Pazare, Amar R.; Mehta, Pankti K. (International Journal of Advances in Medicine, 2018)
Background: Smoking is established as a causative risk factor for COPD as early as 1950. However, in the past decade it is shown that, other risk factors like indoor and outdoor air pollutants, workplace exposure to dust and fumes, poor nourishment and poor socioeconomic status are also associated with COPD. COPD is a disease associated poor quality of life due to recurrent exacerbations. Till to date focus has been on smoking as a risk factor for COPD, but other factors also need to be taken into consideration. Methods: Study was conducted in 60 eligible patients from urban area for a period of 18 months. Individual patient was asked detailed personal demographic data, respiratory symptoms, exposure to passive smoking, family history of COPD. Detailed physical examination including Anthropometric measurements and other relevant general and systemic examination was carried out. Biochemical investigations, ECG, Chest X-ray, CT chest, spirometry and 2D echocardiography were carried out in all patients. Results: The mean age of the patient was 65.7±7.95 with male preponderance. Common symptoms were dyspnea and cough and common signs were rhonchi and hyper resonance note on percussion. Common risk factors were indoor air pollution and low socioeconomic class. Most of the patients has hypoxia and hypercapnia. X-ray chest and CT chest showed hyperinflation, air trapping. Majority of patients had moderate FEV/FVC ratio on spirometry. Conclusions: Non-smoker COPD patients usually present in old age. Common presentation is dyspnea followed by cough and rhonchi on examination. Most common risk factor for non- smoker COPD is indoor air pollution, low socioeconomic class and cotton mill workers. Amongst indoor pollution, LPG, kerosene and wood are the risk factors for non-smokers COPD in urban population.